The politics of kith and kin: Observations on the British Columbia government’s reaction to the death of Sherry Charlie - Cradock, Gerald (First Peoples Child & Family Review, 2007)
This paper examines the events that occurred in British Columbia following the death of a First Nations child placed in a Kith and Kin arrangement. The paper, drawing extensively from internal government reports that were only just recently released to public, provides an “insider’s” view of government sponsored child welfare polices and practices in relation to First Nations child welfare agencies and the communities they serve.